2023
DOI: 10.3389/fpubh.2023.1117518
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intention with remote health management service among urban older adults: A Unified Theory of Acceptance and Use of Technology perspective

Abstract: BackgroundAlthough older adults health management systems have been shown to have a significant impact on health levels, there remains the problem of low use rate, frequency of use, and acceptance by the older adults. This study aims to explore the significant factors which serve as determinants of behavioral intention to use the technology, which in turn promotes actual use.MethodsThis study took a total of 402 urban older adults over 60 years to explore the impact of the use behavior toward remote health man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Ma et al researched the effect of novel and environmentally friendly foods on consumer acceptance and found that PV had a significantly positive effect on attitude, and attitude also had a positive effect on purchase intention 46 . In Li et al’s study, PV positively affected the behavioral intention of older adults to use remote health management services 47 . These studies showed a positive association between PV, intention, and behavior.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ma et al researched the effect of novel and environmentally friendly foods on consumer acceptance and found that PV had a significantly positive effect on attitude, and attitude also had a positive effect on purchase intention 46 . In Li et al’s study, PV positively affected the behavioral intention of older adults to use remote health management services 47 . These studies showed a positive association between PV, intention, and behavior.…”
Section: Discussionmentioning
confidence: 94%
“…Values guide, motivate, and influence attitudes and behaviors 45 . Although direct comparisons cannot be made, owing to the lack of reports examining the association between PV and actual engagement in health behaviors, consumer science research has focused on the relationship between PV and attitudes and intentions 22 , 46 , 47 . Ma et al researched the effect of novel and environmentally friendly foods on consumer acceptance and found that PV had a significantly positive effect on attitude, and attitude also had a positive effect on purchase intention 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, performance expectancy is often considered to be a stronger predictor, as individuals are more likely to adopt and use technology that they believe will improve their performance and meet their goals. Studies have also shown that performance expectancy can also have a positive influence on effort expectancy ( Sung et al, 2015 ; Fedorko et al, 2021 ; Li et al, 2023 ), as individuals may be more willing to put in the effort to learn and use a technology if they believe it will have a positive impact on their performance. However, effort expectancy can also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of SI and FC on BI can vary depending on the specific context. For example, Li et al (2023) reported a statistically nonsignificant relationship between FC and BI in a remote health management service context and Batucan et al (2022) found that SI has no significant impact on BI in an online learning system context.…”
Section: Discussionmentioning
confidence: 99%
“…The TAM has served as a valuable framework for assessing the elderly's perception and acceptance of various healthcare technologies. In the realm of telehealth, TAM can be employed to gauge how elderly individuals perceive and embrace remote consultations, monitoring, and virtual care technologies [24,28,34,[37][38][39][40][41][42][43][44][81][82][83][84]. Furthermore, TAM has been proven useful in understanding the factors influencing the adoption of wearable health devices among the elderly, including smartwatches and fitness trackers designed to monitor vital signs and activity levels [28,45,46].…”
Section: Application Areas Of Tam In Elderly Healthcarementioning
confidence: 99%